Review—Progress in Electrolytes for Rechargeable Aluminium Batteries. Issue 5 (12th May 2021) - Leung, Oi Man; Schoetz, Theresa; Prodromakis, Themis; Ponce de Leon, Carlos
Abstract : The growing demand for safe, sustainable and energy-dense energy storage devices has spurred intensive investigations into post-lithium battery technologies. Rechargeable aluminium batteries are promising candidates for future electrochemical energy storage systems due to the high theoretical volumetric capacity of aluminium and its natural abundance in the Earth's crust, but their practical application is currently hindered by the limitations of presently available electrolytes. In this review, we highlight the key considerations needed to optimise the electrolyte design in relation to the aluminium battery system and critically assess the current state of knowledge and new concepts in liquid and quasi-solid polymer electrolytes, focusing primarily on non-aqueous systems. We then discuss the challenges and approaches in developing polymer electrolytes and finally provide an overview of the opportunities in quasi-solid electrolytes which could pave the way to achieving further improvements in aluminium batteries.